Role of emotional intelligence on rock climbing performance - Garrido-Palomino, I.; Espana-Romero, V. (Revista Internacional de Ciencias del Deporte, 2019)
Purpose: To investigate the association between emotional intelligence (EI) and self-reported climbing ability. Methods: Redpoint climbing ability was used as an indicator of rock climbing performance and EI were assessed as ability and a trait using two different questionnaires MSCEIT and SSEIT in forty-three climbers (15 females and 28 males). ANOVA was used to analyse differences between male and female and advanced and elite climbers in EI parameters in both questionnaires. The analyses were also adjusted by age using ANCOVA. Results: Linear regression analysis revealed that there are no differences between trait EI and climbing performance, but we found the component `Facilitation Thought` of EI measured as ability was inversely associated with the highest red-point ability. Conclusion: Our results suggest that elite climbers do not use their emotions to facilitate thinking as much as expert climbers, which is positively related to performance. Future researches should direct to investigate how elite climbers manage their emotions. (PDF) Role of emotional intelligence on rock climbing performance. [El rol de la inteligencia emocional en el rendimiento en escalada].. Available from: https://www.researchgate.net/publication/334143336_Role_of_emotional_intelligence_on_rock_climbing_performance_El_rol_de_la_inteligencia_emocional_en_el_rendimiento_en_escalada.